Komitmen dan Realitas: Menjawab Defisit Perlindungan terhadap Anak Pengungsi Tanpa Pendamping di Indonesia - Nono, Johanes De Brito Siga; Dollu, Daud Yaferson (Kajian Ilmiah Hukum dan Kenegaraan, 2024)
Purpose: To examine the protection challenges faced by unaccompanied refugee children in Indonesia and evaluate the gaps in the country’s legal and policy framework, particularly in light of its obligations under the Convention on the Rights of the Child (CRC). Methodology: This study uses a normative and prescriptive legal analysis to assess Indonesia’s national laws and policies, including Presidential Regulation No. 125 of 2016, against international human rights standards. Result: The analysis reveals significant gaps in policy implementation, particularly regarding early identification, risk assessment, and access to basic services such as education, healthcare, and legal aid for unaccompanied refugee children. Conclusions: Substantive legal reform, institutional capacity building, and stronger collaboration with international organizations and civil society are essential to ensure effective and humane protection based on the best interests of the child. Limitations: The study is limited to a normative legal analysis and does not include empirical fieldwork or direct perspectives from refugee children or service providers. Contribution: This article contributes to the discourse on child protection in refugee contexts by offering concrete policy recommendations aligned with international legal standards and rooted in the principles of the CRC, filling a critical gap in the Indonesian legal framework.